Physical Activity Levels of Adult Virtual Football Players - Pereira, Ana M.; Verhagen, Evert; Figueiredo, Pedro; Seabra, André; Martins, António; Brito, João (Frontiers in Psychology, 2021)
Esports, including virtual football, are a worldwide phenomenon. Yet, little is known about the physical activity levels of individuals engaged in virtual football game play. Therefore, we aimed to perform a preliminary evaluation of the levels of physical activity, sedentarism and habits of physical training of adults engaged with virtual football in Portugal. This was a cross-sectional investigation based on a structured online survey using the International Physical Activity Questionnaire (IPAQ) and a set of questions regarding habits of physical training. The participants (n = 433) reported spending a median of 5,625 MET-min·week-1 being physically active. Still, the participants spent 320 min/day sitting, and 150 min/day practicing virtual football. According to the IPAQ scores, high physical activity levels were reported by 84.5% of the participants, and 87.1% were considered physically active considering the WHO guidelines on physical activity and sedentary behavior. Overall, 60.0% of the participants reported planning their own physical training. Maintaining or improving overall physical health was one of the main reasons for doing physical training (66.7%), with only 6.1% responding being active to improve virtual football performance. Overall, the results showed that virtual football players accomplished the standard recommendations for physical activity, with high levels of physical activity, and encompassing regular physical training focused mostly on health promotion, rather than improved virtual football performance.